Determination of The SPF Value of Onion Extract (Allium Cepa L) and Kecomrang Leaves (Etlingera Elatior) A Systematic Review - Rhamal Amir; Nisa Sri Wahyuni; Nisa Alwia; Azahra Aqila; Silfia Ismiati; Aden Dhana Rizkita (Proceeding International Conference on Religion, Science and Education, 2023)
Ultraviolet (UV) rays are sunlight that can be harmful to the skin. Sunscreen is generally used when handling. Sunscreen is a product that is intended to protect the skin from damage caused by UV rays of the sun, with formulations that are able to protect against UV-A and UV-B rays. Sunscreens have different SPF values. The SPF value is a measure of the amount of ultraviolet radiation used to burn the skin when exposed to sunlight protected by sunscreen. Therefore, the SPF value indicates the ability of a sunscreen to reduce the harmful effects caused by UV rays. Indonesia has around 30.000-50.000 plant species, but there are many medicinal plants such as kecombrang leaves and shallot skin. Only about 7.500 of the species available for it contain phenolic and flavonoid compounds that provide UV protection and have sunscreen potential. The SPF test uses maceration extracted samples. The solvents used were water and ethanol and tested with a UV-Vis spectrophotometer. The test results showed that 300 ppm kecombrang leaf water extract had the highest SPF value and an additional sun protection power of 7.30 ± 0.62. The n-hexane fraction of kecombrang leaves showed the best protection with an SPF of 17.57 ± 2.49 at a UV protection level of 300ppm. The ethyl acetate fraction had the highest SPF value, namely 2.65 ± 0.12 in the least protected class. From the results of the shallot skin extraction test, the SPF value of the differences in concentrations of 4ppm, 8ppm, 12ppm and 16ppm was 11.44 each. 20:12; 30.80 and 34.83. The optimum concentration of shallot skin is 16ppm with an SPF value of 34.83. As a result of data analysis, it was found that the ethanol extract of shallot skin had a higher sunscreen effect than the aqueous extract of kecombrang leaves.